Metabolism of Exogenous D-Beta-Hydroxybutyrate, an Energy Substrate Avidly Consumed by the Heart and Kidney - Cuenoud, Bernard; Hartweg, Mickaël; Godin, Jean-Philippe; Croteau, Etienne; Maltais, Mathieu; Castellano, Christian-Alexandre; Carpentier, André C.; Cunnane, Stephen C. (Frontiers in Nutrition, 2020)
There is growing interest in the metabolism of ketones owing to their reported benefits in neurological and more recently in cardiovascular and renal diseases. As an alternative to a very high fat ketogenic diet, ketones precursors for oral intake are being developed to achieve ketosis without the need for dietary carbohydrate restriction. Here we report that an oral D-beta-hydroxybutyrate (D-BHB) supplement is rapidly absorbed and metabolized in humans and increases blood ketones to millimolar levels. At the same dose, D-BHB is significantly more ketogenic and provides fewer calories than a racemic mixture of BHB or medium chain triglyceride. In a whole body ketone positron emission tomography pilot study, we observed that after D-BHB consumption, the ketone tracer 11C-acetoacetate is rapidly metabolized, mostly by the heart and the kidneys. Beyond brain energy rescue, this opens additional opportunities for therapeutic exploration of D-BHB supplements as a ‘super fuel’ in cardiac and chronic kidney diseases.